2020
DOI: 10.3390/cancers12113369
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Profiles of ADME Genes in Human Cancers and Their Associations with Clinical Outcomes

Abstract: ADME genes are a group of genes that are involved in drug absorption, distribution, metabolism, and excretion (ADME). The expression profiles of ADME genes within tumours is proposed to impact on cancer patient survival; however, this has not been systematically examined. In this study, our comprehensive analyses of pan-cancer datasets from the Cancer Genome Atlas (TCGA) revealed differential intratumoral expression profiles for ADME genes in 21 different cancer types. Most genes also showed high interindividu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 94 publications
3
23
0
Order By: Relevance
“…We identified for the first time a PXR-mediated role of SLC16A1 in the transport of afatinib and the sensitivity of prostate cancer cells to this ErBb family blocker. Our study further strengthens the implication of ADME genes in the clinical outcome of various cancers [ 55 ] and highlights the importance of PXR as a potential biomarker of response to anticancer treatments in prostate cancers, in particular kinase inhibitors that are still the object of many clinical trials for castration-resistant tumors.…”
Section: Discussionsupporting
confidence: 76%
“…We identified for the first time a PXR-mediated role of SLC16A1 in the transport of afatinib and the sensitivity of prostate cancer cells to this ErBb family blocker. Our study further strengthens the implication of ADME genes in the clinical outcome of various cancers [ 55 ] and highlights the importance of PXR as a potential biomarker of response to anticancer treatments in prostate cancers, in particular kinase inhibitors that are still the object of many clinical trials for castration-resistant tumors.…”
Section: Discussionsupporting
confidence: 76%
“…The samples were from Japanese individuals [ 17 ]. A set of ADME-related genes ( n =298) was acquired from previous literature [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have explored the role of ADME genes as prognostic cancer biomarkers and therapeutic targets. Hu et al (14) reported that about half of ADME genes are expressed in 21 cancers and they have prognostic value in these cancers. In addition, most ADME genes are highly expressed in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…As a varying number of UGT genes were expressed in different cancer types (Table S1), the number of independent logrank tests performed varied among different cancers, ranging from 20 tests in LIHC to 3 tests in UVM. To control false-positive discovery rates, we adjusted the logrank p-values for each cancer type using Bonferroni correction, the most stringent test for multiple testing correction as recently reported [41]. A Bonferroni-corrected cutoff logrank p-value of <0.05 was considered statistically significant.…”
Section: Assessment Of Associations Between the Intratumoral Expression Levels Of Ugt Genes And Overall Survival Of Cancer Patients Usingmentioning
confidence: 99%
“…The Cancer Genome Atlas (TCGA) project analysed over 20,000 primary cancer patients from 33 different cancer types and provides freely-accessible databases for genomewide molecular profiles (e.g., RNAseq datasets) as well as clinicopathological data (e.g., survival times) for cancer patients (https://gdc.cancer.gov, accessed on 20 June 2021) [40]. Using the RNAseq and clinical datasets from the TCGA project, we recently reported the expression profiles of core ADME genes and their association with patient survival in 21 different TCGA cancer types [41]. Through analyses of the RNAseq and clinical datasets from the TCGA project, the present study defines the expression profiles of all UGT genes in 33 different TCGA cancer types and reports a subset of UGT genes that are significantly associated with survival rates in specific cancers.…”
Section: Introductionmentioning
confidence: 99%